Black Fathers' Participation in Early Childhood Development in South Africa: What Do We Know?. (1st March 2016) - Mncanca, M.; Okeke, C.I.O.; Fletcher, R.
Abstract: This paper draws from an ongoing exploratory qualitative study, which uses semi-structured interviews to investigate the views of fathers about strategies to encourage men's participation in early childhood education in one of the townships in the Eastern Cape Province. The study aims to contribute to knowledge about fathers' participation in early childhood education in general and on the participation of black fathers in particular. Informed by Uriel Bronfenbrenner's ecological model, the literature review explores the current state of fathers' participation during the early beginning of the child; barriers to sustained fathers' participation; and current strategies in place to encourage sustainable and meaningful father participation in the early education of their children. This paper argues that what is currently known about black fathers' participation in the early education of their children is grossly inadequate. Given limited information on Black fathers' participation in the education of their children in South Africa, this paper concludes that more research on Black fathers and their participation in early education of children is therefore required. Some implications for research and policy are also discussed.